Agresividad impulsiva y premeditada en niños y niñas - Pérez Sánchez, Karen Estefanía (2021)
This study aims to determine the elements that make up impulsive and premeditated aggressiveness. The importance of the research lies in the exhaustive review of theoretical references that explain the category of analysis. From the methodological point of view, the research was of a qualitative approach since the bibliographic type was used to collect information to construct the bibliographic review matrix. The technique used was the bibliographic review and the instrument, the data review matrix. The collection of information shows that aggressiveness is a momentary emotion in which the desire for authority, leadership, and respect may predominate. From the research carried out, it is evident that aggressiveness has been normalized due to social environment, family environment, and free use of technologies without content control by adults. The main consequences of aggressiveness are emotional instability, anxiety, low self-esteem. Finally, it was established that boys are more likely to manifest impulsive aggressive behaviors while girls express premeditated and mixed aggressiveness.